Síntese, caracterização e avaliação antitumoral de novos derivados 3-Benzil-5-(Indol-3-il-Metileno)-Tiazolidina-2,4-Diona - Christianne Batista de Lacerda Pedrosa, Sybelle (2011)
The thiazolidine-2,4-dione are a class of compounds derived thiazolidine. It is a 5-membered ring containing a sulfur atom and a nitrogen atom in positions 1 and 3, respectively, and carbonyl in position 4 and 2. Data in the literature demonstrate the synthetic thiazolidinedione ligands of PPARs as and therefore play some biological activities such as hypoglycemic, antimicrobial, antitumor and anti-inflammatory. This study aimed to: synthesize new derivatives 5 - (indole-3-yl-methylene)-3-benzyl-thiazolidine-2 ,4-dione, by reactions of cyclization, addition of Michael, N-alkylation at position 3 and in the Knoevenagel condensation at position 5 of ring thiazolidine-2,4-dione. The molecules obtained were proved by infrared spectroscopic methods, hydrogen nuclear magnetic resonance and mass spectrometry. It was found that in vitro cytotoxicity of new molecules synthesized in three tumor cell lines: HT29 (colon carcinoma - human), HEP (laryngeal carcinoma - human) and NCI H-292 (human lung cancer). This analysis was part of an initial screening to determine the antitumor potential. The 3-(3-bromo-benzyl)-5-(5-bromo-1H-indole-3-yl-methylene)-thiazolidine-2,4-dione (LPSF/GQ-240) showed the best result for NCI H-292 (human lung cancer) 80.2% of inhibition and HT29 (colon carcinoma - human) 83.1% of inhibition. This antitumor activity in vivo was performed in the model where the Sarcoma-180 which showed high values of inhibition of tumor growth in three doses tested (10, 20 and 40mg/kg) of LPSF/GQ-240 compared to the negative control. These results confirm the importance of derivatives 5-(indole-3-yl-methylene)-3-benzyl-tiazolodina-2,4-dione in the fight against cancer.